TINGKAT DISIPLIN DAN TANGGUNG JAWAB PESERTA DIDIK YANG MENGIKUTI EKSTRAKURIKULER DI SMAN 1 TELUK BATANG - Kurniawan, Nanang; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe problem in this study is the number of violations relating to behavior, character, sopa polite towards students. The purpose of this study is to find out how much the level of discipline and responsibility of students who take extracurricular activities at SMAN 1 Teluk Batang.The method used in this research is quantitative descriptive method with quantitative descriptive survey form. The population in this study were students who participated in extracurricular activities with 50 samples. Sampling in this study uses random sampling. Retrieval of data using direct observation. The instrument used is a questionnaire.Based on the calculation of the data obtained, namely the level of discipline of students who take extracurricular activities, 2% are very good categories, 86% are good categories, 12% are poor categories. While the level of responsibility of students who take extracurricular activities, 4% is very good category, 84% good category, 12% less category. Thus the conclusion of this study is the levelof discipline and responsibility for taking extracurricular activities at SMAN 1 Teluk Batang classified as good.Keywords: Dicipline, Responsible, Extracurricular